2017
DOI: 10.1007/s11017-017-9415-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the UK House of Commons Science and Technology Committee’s position on the implausible effectiveness of homeopathic treatments

Abstract: In 2009, the UK House of Commons Science and Technology Committee (STC) conducted an ‘evidence check’ on homeopathy to evaluate evidence for its effectiveness. In common with the wider literature critical of homeopathy, the STC report seems to endorse many of the strong claims that are made about its implausibility. In contrast with the critical literature, however, the STC report explicitly does not place any weight on implausibility in its evaluation. I use the contrasting positions of the STC and the wider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…(3) medium stress with neutralised effects; (4) severe stress with a significant growth-inhibiting effect after homeopathic treatment; and (5) very severe stress without homeopathic treatment effect (►Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…(3) medium stress with neutralised effects; (4) severe stress with a significant growth-inhibiting effect after homeopathic treatment; and (5) very severe stress without homeopathic treatment effect (►Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…It pertains to excessive service by prescription of unnecessary medical treatments and procedures (Connell, 2013). Second, there is growing Scepticism in academia towards the holistic, therapeutical approach because several studies have reported their questionable outcomes (Turner, 2017; Pinilla and Rodriguez-Caro, 2019). Third, several treatment solutions, including surrogacy, stem cells, abortion, transplantation and “death tourism” (euthanasia), raise concern over patient safety and human morality (Connell, 2013).…”
Section: Future Perspective 75 Years 2020-2095mentioning
confidence: 99%
“…By some measures homeopathy is now one of the most popular forms of complementary and alternative medicine (CAM), with particularly high usage in northern Europe (Ernst, 2016; Fischer et al, 2014; Hart, 2018; Ong et al, 2005) where it is delivered as part of the national healthcare systems in countries including the UK (Turner, 2017), Denmark and France (Frank, 2002). However, as a paradigm, homeopathy is essentially ‘heretical’ (Jones, 2004) as it breaches central tenets of the orthodox Western model (Turner, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By some measures homeopathy is now one of the most popular forms of complementary and alternative medicine (CAM), with particularly high usage in northern Europe (Ernst, 2016; Fischer et al, 2014; Hart, 2018; Ong et al, 2005) where it is delivered as part of the national healthcare systems in countries including the UK (Turner, 2017), Denmark and France (Frank, 2002). However, as a paradigm, homeopathy is essentially ‘heretical’ (Jones, 2004) as it breaches central tenets of the orthodox Western model (Turner, 2017). In particular, it uses highly diluted treatments that are said (by Western medicine) to contain no molecular content other than water (Cucherat et al, 2000); it tailors treatments to individuals rather than using a generalised evidence base of effectiveness to make prescription decisions; and it often uses one treatment to cure multiple ailments, rather than using combinations of treatments.…”
Section: Introductionmentioning
confidence: 99%